CORRELATION BETWEEN ECONOMIC GROWTH AND PUBLIC DEBT LEVEL IN SELECT COUNTRIES OF THE EUROPEAN UNION - Sobczak, Wioleta; Radziewicz, Elżbieta (Acta Scientiarum Polonorum. Oeconomia, 2021)
The complex correlation between public debt and economic growth is very important and is a focus of research within the scientific community and among policy makers. The main purpose of this paper is to identify the correlation between the level of public debt and the level of economic growth in select European Union countries. It is an empirical study of the transmission mechanisms and impact of public debt on economic growth in countries which joined the European Union in 2004 or later. The time range of the analyses covers the years 2000–2019. Estimation of the model parameters shows that the level of public debt had an impact on economic growth only in some countries.